2020
DOI: 10.1155/2020/4965670
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Studying the Role and Molecular Mechanisms of MAP4K3 in Sorafenib Resistance of Hepatocellular Carcinoma

Abstract: Sorafenib is the first FDA-approved therapeutic drug for molecular target medication on advanced-stage hepatocellular carcinoma. It is reported that sorafenib could improve the survival of progression-free patients for 4 to 6 months; however, most of the patients developed drug resistance. Thus, it is critical to reveal the biological mechanisms behind sorafenib resistance. In this study, a sorafenib-resistant model was developed by exposing HepG2 cells to sorafenib with gradient increasing concentration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…E2 binds to its acceptor ER, and proto-oncogene tyrosine-protein kinase Src (c-Src) is phosphorylated by ER, and subsequent c-Src activates Ras. Activated Ras regulates the ERK pathway, in turn triggering kinase activity of proteins Raf, MEK, and ERK [ 47 49 ]. E2-stimulated ERK promotes RNA transcription of the Fra1 gene and phosphorylation of Fra1 protein, which in turn inducted ZEB1/2.…”
Section: Molecular Mechanismmentioning
confidence: 99%
“…E2 binds to its acceptor ER, and proto-oncogene tyrosine-protein kinase Src (c-Src) is phosphorylated by ER, and subsequent c-Src activates Ras. Activated Ras regulates the ERK pathway, in turn triggering kinase activity of proteins Raf, MEK, and ERK [ 47 49 ]. E2-stimulated ERK promotes RNA transcription of the Fra1 gene and phosphorylation of Fra1 protein, which in turn inducted ZEB1/2.…”
Section: Molecular Mechanismmentioning
confidence: 99%
“…Patients with MGMT promoter methylation were more sensitive to temozolomide (TMZ) chemotherapy and had a better prognosis [ 10 ]. BRAF (v-raf murine viral oncogene homolog B1) mutations were found in pilocytic astrocytomas and have been proved to be a new therapeutic target for inhibition of the mitogen-activated protein kinase (MAPK) cascade, but its prognostic significance is unknown [ 11 ]. Vemurafenib, as a BRAF inhibitor, can have a complete clinical regression of relapsed glioblastoma multiforme [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%